INFLUENCE OF 4A ZEOLITE SYNTHESIS PROCESS PARAMETERS ON WATER SORPTION CAPACITY - Janković, M.; Tanasijević, A.; Filipović, R.; Perušić, M. (Journal of Engineering & Processing Management, 2014)
This paper studies the effect of process parameters on the sorption characteristics of zeolite 4A. The observed process are related to the influence of crystallization temperature, crystallization time and influence concentrations of Na2O. In parallel with the examination of the impact of these parameters on the capacity of water sorption of zeolite 4A, which was the primary goal, are analyzedinfluence on the adsorption capacity of dibutyl phthalate (DBF) synthesized powders as well as crystallinity and average size of the resulting particles of the zeolite. The results show that the capacity of water sorptione zeolite 4A increases with temperature and crystallization time, and decreased with increasing concentrations of Na2O. The influence of given parameters DBF adsorption, and the mean particle size is less prominent. Crystallinity also shows a significant dependence on temperature.